Uranium Immobilization by Sulfate-Reducing Biofilms - Beyenal, Haluk; Sani, Rajesh K; Peyton, Brent M; Dohnalkova, Alice C; Amonette, James E; Lewandowski, Zbigniew (Environmental science & technology, 2004)
Hexavalent uranium [U(VI)] was immobilized using biofilms of the sulfate-reducing bacterium (SRB) Desulfovibrio desulfuricans G20. The biofilms were grown in flat-plate continuous-flow reactors using lactate as the electron donor and sulfate as the electron acceptor. U(VI) was continuously fed into the reactor for 32 weeks at a concentration of 126 μM. During this time, the soluble U(VI) was removed (between 88 and 96% of feed) from solution and immobilized in the biofilms. The dynamics of U immobilization in the sulfate-reducing biofilms were quantified by estimating:  (1) microbial activity in the SRB biofilm, defined as the hydrogen sulfide (H2S) production rate and estimated from the H2S concentration profiles measured using microelectrodes across the biofilms; (2) concentration of dissolved U in the solution; and (3) the mass of U precipitated in the biofilm. Results suggest that U was immobilized in the biofilms as a result of two processes:  (1) enzymatically and (2) chemically, by reacting with microbially generated H2S. Visual inspection showed that the dissolved sulfide species reacted with U(VI) to produce a black precipitate. Synchrotron-based U L3-edge X-ray absorption near edge structure (XANES) spectroscopy analysis of U precipitated abiotically by sodium sulfide indicated that U(VI) had been reduced to U(IV). Selected-area electron diffraction pattern and crystallographic analysis of transmission electron microscope lattice-fringe images confirmed the structure of precipitated U as being that of uraninite.